Modeling the effect of hyperoxia on the spin–lattice relaxation rate R1 of tissues - Bluemke, E; Stride, E; Bulte, DP (Wiley, 2022)
Purpose Inducing hyperoxia in tissues is common practice in several areas of research, including oxygen-enhanced MRI (OE-MRI), which attempts to use the resulting signal changes to detect regions of tumor hypoxia or pulmonary disease. The linear relationship between PO2 and R1 has been reproduced in phantom solutions and body fluids such as vitreous fluid; however, in tissue and blood experiments, factors such as changes in deoxyhemoglobin levels can also affect the ΔR1.